Edukasi Pengelolaan Sampah Plast Edukasi Pengelolaan Sampah Plastik Melalui Sosialisasi dan Pembuatan Ecobrick - Muthi'Uddin, Ahmad; Zainuddin, Moh.; Afiktaputra, Mochamad Alfianudin; Wijayanti, Arie Devi; Setyo, Surya Desdi (Insan Kreasi Media, 2025)
Plastic waste remains a pressing issue both nationally and locally, including within primary education environments. The lack of children’s awareness regarding the impacts of plastic waste makes schools a strategic point for environmental education. A community service activity through KKN UNUGIRI 2025 in Bakulan Village was carried out in the form of waste-sorting socialization and ecobrick-making practice at SDN Bakulan 2. The main objective of this program was to increase students’ knowledge, skills, and environmental awareness regarding plastic waste management through practical and engaging activities. A tangible impact was seen in students beginning to collect plastic waste in their classrooms and schoolyard. This activity aligns with the efforts to achieve the SDGs, particularly Goal 12 (Responsible Consumption and Production) and Goal 13 (Climate Action). The program is recommended to be continued through class-based ecobrick competitions and the integration of environmental education into the elementary school curriculum